THE INFLUENCE OF PRODUCT DESIGN, SALES PROMOTION AND PRODUCT QUALITY ON CUSTOMER PURCHASE DECISION AT CONVERSE SHOES (STUDY ON MILLENIAL GENERATION): Article - Christina Heti Tri Rahmawati; Tjhai Catherine Tanuwijaya; Albertus Yudi Yuniarto (MANAJEMEN DEWANTARA, 2022)
This study aim to determinate: (1) the influence of product design, sales promotion and product quality simultaneously on customer purchase decision at Converse, (2) the influence of product design partially on customer purchase decision at Converse, (3) the influence of sales promotion partially on customer purchase decision at Converse, (4) the influence of product quality partially on customer purchase decision at Converse. This sampling technique uses a non-probability sampling method with purposive sampling technique. The population of this research are millenial generation which is at the age of 21- 40 years. The sample of this research is 100 respodent of millenial generation who already purchased and used Converse shoes and the data was obtained by distributing questionnaires. The data analysis technique used in this study is descriptive analysis, classical assumption test, and multiple linear regression analysis using the SPSS 23 application. The results of the study show that: (1) product design, sales promotion and product quality simultaneously influenced consumer purchase decision, (2) product design partially influenced consumer purchase decision, (3) sales promotion partially influenced consumer purchase decision, (4) product quality partially influenced consumer purchase decision.